Experiencias docentes en la implementación de estrategias metodológicas para la comprensión lectora - Contreras Tapahuasco, Hentz Dona (2016)
The present research pedagogical action represents a very fundamental axis for the pedagogical practice, in order to manage the teaching task through the design of methodological strategies. This document will review the concepts of strategies for reading comprehension, teaching practice focused on research pedagogical action and improvement of learning and teaching processes.